HUMAN RIGHTS - A CONCEPT WITH UNIVERSAL MEANINGS - Isabela STANCEA (Strategii Manageriale, 2012)
The concept of human rights has evolved in its essence as physical force was gradually replaced by reason, as in society took shape legal principles that would become fundamental: the principle of freedom, equality, solidarity, etc.. Fundamental human rights are a set of rights, freedoms and duties recognized worldwide covering essential issues for human development, welfare and progress. Over time, the human rights institution has evolved and undergone important correctives from one historical arrangement to another and bet on the same order, from one stage to another.